HAKIKAT MANAJEMEN STRATEGI PENDIDIKAN ISLAM - Jusniati Jusniati; Mualimah Mualimah; Muh. Imaduddin Basarang (IQRA : JURNAL MAGISTER PENDIDIKAN ISLAM, 2022)
Strategic management is a process carried out in achieving the goals to be achieved, which have a future orientation with the support of strategies that can be carried out and implemented in seeing opportunities and anticipating various kinds of threats that might occur in an organization.Thus a conclusion can be drawn that the strategic management process focuses on a decision or policies to be taken in preparing for future competition as well as managerial and building motivation for all existing components, to have high work motivation.